Pattern of Histopathological Grades of Astrocytoma Patients attended at a Tertiary Care Hospital in Dhaka City (Journal of National Institute of Neurosciences Bangladesh, 2024)
Background: Different grades of astrocytomas are presented as the variant of brain tumour.Objective: The purpose of the present study was to evaluate the frequency and distribution of different grades of astrocytoma patients.Methodology: This cross sectional study was carried out in the Department of Radiology and Imaging with the collaboration of Department of Neurosurgery and Department of Pathology at Sir Salimullah Medical College (SSMC & MH), Dhaka from January 2013 to December 2013 for a period of one (1) year. Patients presented with clinically diagnosed cases of intracranial astrocytoma who were attended in the OPD and IPD were selected as study population. The postoperative resected tissues were histopathological examined in the respective department.Result: The sample size of the present study was 48 astrocytoma patients. The mean age (±SD) was 39.96 years (±12.440). During MRI pilocytic astrocytoma, low grade astrocytoma, anaplastic astrocytoma and glioblastoma multiformis are found in 8.3% cases, 31.2% cases, 52.1% cases and 52.1% cases respectively.Conclusion: MRI is an effective tool for the diagnosis of astrocytoma.Journal of National Institute of Neurosciences Bangladesh, July 2023;9(2):147-150